The growth-employment-poverty nexus in Latin America in the 2000s: Panama country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Between 2000 and 2012, Panama boasted the strongest economic growth in Latin America. The growth experience was not uniform: the 2000-02 period was marked by slow or negative growth rates, after which growth was exceptionally rapid. Although the international economic crisis of 2008 slowed the growth process down, it rebounded in the years following the crisis. Labour market indicators have clearly improved. The economic crisis led to a temporary increase in unemployment, a drop in the share of paid employees, and a rise in some poverty indicators; all these effects were reversed by the end of the period studied.
Keywords: O15; J01; J30; 330; Panama; Latin America; inclusive growth; labour market; poverty